The use of carbon based materials for improving methane production from ethanol anaerobic fermentation : Viability analysis and fertilizer recovery - Siddique, Md Nurul Islam; Zaied, Khalid; Noraaini, Ali; Mohd Zamri, Ibrahim; Shahrul, Ismail (Asian Publication Corporation, 2022)
The impacts of carbon-based sources on anaerobic digestion methane generation were investigated in this study. The study revealed that bio-solids and hydrochars may increase accumulative methane output by 16% to 30%. Nevertheless, there is no significant difference (statistically) (p > 0.05) in methane production from hydrochars and biosolids generated at, unlike temperatures. Biosolids and hydrochars augmented microorganisms that may contribute indirect interspecies electron transfer. Microorganisms' direct interspecies electron transfer (DIET) in a stable environment created by carbon-based compounds with homogeneous dispersion and electrons were transported via an aromatic functional group on the surface of the material. From the fermented effluent, sludge recapture was 0.09 m3 sludge/m3 wastewater. The time required to recoup investment was calculated to be 3.72 years. This study suggested that the impact of surface characteristics of carbon-based sources on methane generation in anaerobic fermentation and proposes a novel method for reusing discarded tea grounds.